Endothelial Forkhead Box Transcription Factor P1 Regulates Pathological Cardiac Remodeling Through Transforming Growth Factor-β1–Endothelin-1 Signal Pathway. Issue 8 (20th August 2019) - Liu, Jie; Zhuang, Tao; Pi, Jingjiang; Chen, Xiaoli; Zhang, Qi; Li, Ying; Wang, Haikun; Shen, Yajing; Tomlinson, Brian; Chan, Paul; Yu, Zuoren; Cheng, Yu; et al.
Abstract : Background: Pathological cardiac fibrosis and hypertrophy, the common features of left ventricular remodeling, often progress to heart failure. Forkhead box transcription factor P1 (Foxp1) in endothelial cells (ECs) has been shown to play an important role in heart development. However, the effect of EC-Foxp1 on pathological cardiac remodeling has not been well clarified. This study aims to determine the role of EC-Foxp1 in pathological cardiac remodeling and the underlying mechanisms. Methods: Foxp1 EC-specific loss-of-function and gain-of-function mice were generated, and an angiotensin II infusion or a transverse aortic constriction operation mouse model was used to study the cardiac remodeling mechanisms. Foxp1 downstream target gene transforming growth factor-β1 (TGF-β1) was confirmed by chromatin immunoprecipitation and luciferase assays. Finally, the effects of TGF-β1 blockade on EC-Foxp1 deletion–mediated profibrotic and prohypertrophic phenotypic changes were further confirmed by pharmacological inhibition, more specifically by RGD-peptide magnetic nanoparticle target delivery of TGF-β1–siRNA to ECs. Results: Foxp1 expression is significantly downregulated in cardiac ECs during angiotensin II–induced cardiac remodeling. EC-Foxp1 deletion results in severe cardiac remodeling, including more cardiac fibrosis with myofibroblast formation and extracellular matrix protein production, as well as decompensated cardiac hypertrophy and further exacerbation of cardiac dysfunction on angiotensin II infusion or transverse aortic constriction operation. In contrast, EC-Foxp1 gain of function protects against pathological cardiac remodeling and improves cardiac dysfunction. TGF-β1 signals are identified as Foxp1 direct target genes, and EC-Foxp1 deletion upregulates TGF-β1 signals to promote myofibroblast formation through fibroblast proliferation and transformation, resulting in severe cardiac fibrosis. Moreover, EC-Foxp1 deletion enhances TGF-β1–promoted endothelin-1 expression, which significantly increases cardiomyocyte size and reactivates cardiac fetal genes, leading to pathological cardiac hypertrophy. Correspondingly, these EC-Foxp1 deletion–mediated profibrotic and prohypertrophic phenotypic changes and cardiac dysfunction are normalized by the blockade of TGF-β1 signals through pharmacological inhibition and RGD-peptide magnetic nanoparticle target delivery of TGF-β1–siRNA to ECs. Conclusions: EC-Foxp1 regulates the TGF-β1–endothelin-1 pathway to control pathological cardiac fibrosis and hypertrophy, resulting in cardiac dysfunction. Therefore, targeting the EC–Foxp1–TGF-β1–endothelin-1 pathway might provide a future novel therapy for heart failure. Abstract : Supplemental Digital Content is available in the text.